Penerapan etika bisnis untuk meningkatkan kualitas kinerja karyawan pada perbankan syariah - Jazilah, Zahrotul (Maliki Interdisciplinary Journal, 2025)
The application of business ethics in Islamic banking is a guideline in carrying out operations in accordance with sharia principles. The study aims to find out how to apply business ethics can improve the quality of employee performance in Islamic banking. The research method used is literature analysis of related studies. The results of the study show that the application of good business ethics can improve the quality of employee performance in Islamic banking by applying the principles of business ethics and creating a positive work environment. Business ethics practices carried out by employees include honesty, fairness, and social responsibility, which can create customer trust and loyalty. This can motivate employees to improve the quality of their performance.